2003
DOI: 10.1575/1912/2454
|View full text |Cite
|
Sign up to set email alerts
|

Mixing processes and hydraulic control in a highly stratified estuary

Abstract: This thesis utilizes field data from the Fraser River Estuary, a highly stratified system located in southwestern British Columbia, Canada, to investigate the nature of mixing processes in a highly stratified environment, and to extend two-dimensional hydraulic theory to a three dimensional environment.During the late ebb, a stationary front exists at the Fraser mouth. Although densimetric Froude numbers in the vicinity of the front are supercritical in a frame of reference parallel to the local streamlines, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…It is the flux in this lower region that supplies most of the salt to the lift-off zone [MacDonald, 2003] and is most likely to influence the salt balance and thus impact the turbulence calculations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the flux in this lower region that supplies most of the salt to the lift-off zone [MacDonald, 2003] and is most likely to influence the salt balance and thus impact the turbulence calculations.…”
Section: Discussionmentioning
confidence: 99%
“…A separate analysis of data from the 2000 freshet, as discussed by MacDonald [2003], has suggested that the flow in this region of the channel is nearly two-dimensional, particularly above the 20 psu isohaline, based on a three-dimensional salt balance and the relative contribution of lateral (southward-directed) salt flux to the overall salt budget in the region. However, due to the complexities of the interactions between entrainment and turbulence in generating the vertical transport, there are multiple pathways through which lateral fluxes may impact the calculations.…”
Section: Appendix A: Reference Framesmentioning
confidence: 99%
“…Certainly, the scales of river plumes are typically large enough that the effect of the Earth's rotation becomes important in the far field [e.g., Fong, 1998]. In the near field, most river plumes are narrow enough that Coriolis effects are negligible [e.g., Wright and Coleman, 1971;MacDonald, 2003], and in this region the most useful comparisons between industrial plumes and geophysical plumes can be drawn.…”
Section: Implications For Geophysical Plumesmentioning
confidence: 99%
“…Here, the estuary mouth acts as a hydraulic constriction for the upper layer (Armi and Farmer 1986). The accelerating flow soon becomes unstable, and strong shear mixing occurs in the near field (Wright and Coleman 1971;MacDonald 2003). Beyond this region, mixing is primarily caused by wind stress through a mechanism described by Fong and Geyer (2001).…”
Section: Introductionmentioning
confidence: 99%